MEMORI KOLEKTIF DAN LANSKAP PANTAI: REPRESENTASI SEJARAH DAN BUDAYA DALAM NARASI ISATA DI PANTAI ARJUNA - Komang Triawati; Sayu Komang Dewi Yunita; I Gede Putu Awikesa (Jurnal Pariwisata PaRAMA : Panorama, Recreation, Accomodation, Merchandise, Accessbility, 2026)
Arjuna Beach, est Tolai, Parigi Moutong, is a rich cultural landscape that represents the unique collective memory of the Balinese transmigrant community. The symbolism of the name “Arjuna”, the temples, and traditional rituals demonstrate the harmony of nature, culture, and spirituality. This study believes that tourism has the potential to preserve this intangible cultural heritage, going beyond its visual appeal.This research analyzes the representation of local communities' collective memory in tourism narratives at Arjuna Beach. The focus is on identifying historical and cultural manifestations ithin tourist attractions, as ell as the role of the landscape as a medium for representing collective memory. Dra ing on the theory of Maurice Halb achs and inspired by Adi angsa and Suryani (2023), e uncover the hidden narratives that shape the identity of Arjuna Beach. A qualitative case study approach as used, involving observation, in-depth intervie s, and document analysis. Data ere analyzed thematically to understand the internalization of collective memory in tourism and the perspectives of local communities. The results are expected to provide theoretical contributions to tourism science and practical insights for the development of sustainable tourism that integrates culture, history, and ecology, empo ers local communities, and builds a sense of place value.